2019
DOI: 10.1021/acs.jmedchem.8b01938
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Mechanistic Study of Tailor-Made Quinoline Derivatives as Topoisomerase 1 Poison with Potent Anticancer Activity

Abstract: To overcome chemical limitations of camptothecin (CPT), we report design, synthesis, and validation of a quinoline-based novel class of topoisomerase 1 (Top1) inhibitors and establish that compound 28 (N-(3-(1H-imidazol-1-yl)­propyl)-6-(4-methoxyphenyl)-3-(1,3,4-oxadiazol-2-yl)­quinolin-4-amine) exhibits the highest potency in inhibiting human Top1 activity with an IC50 value of 29 ± 0.04 nM. Compound 28 traps Top1–DNA cleavage complexes (Top1ccs) both in the in vitro cleavage assays and in live cells. Point m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 56 publications
3
38
0
Order By: Relevance
“…[17] To investigate whether Ru1-7 are topo poisons,t he formation of topoisomerase-induced DNAstrand breaks was measured. As shown in Figure S13A [11][12][13][14][15][16][17], suggesting that the Ru II complexes act as tep upstream of CPT.S imilar results were observed for topoisomerase II ( Figure S13B). Thepoison VP-16 selectively affects topo II-mediated DNAr e-ligation, which leads to the presence of al inear DNAb and.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…[17] To investigate whether Ru1-7 are topo poisons,t he formation of topoisomerase-induced DNAstrand breaks was measured. As shown in Figure S13A [11][12][13][14][15][16][17], suggesting that the Ru II complexes act as tep upstream of CPT.S imilar results were observed for topoisomerase II ( Figure S13B). Thepoison VP-16 selectively affects topo II-mediated DNAr e-ligation, which leads to the presence of al inear DNAb and.…”
Section: Resultsmentioning
confidence: 61%
“…Them ajority of topo inhibitors are topo poisons and reports on topo I/II dual catalysis inhibitors are rare. [16] This may be due to the structural differences between the two enzymes,r esulting in design difficulties. [17] To investigate whether Ru1-7 are topo poisons,t he formation of topoisomerase-induced DNAstrand breaks was measured.…”
Section: Resultsmentioning
confidence: 99%
“…Live-cell imaging was carried out as described previously ( 12 , 27 , 63 , 64 ). Briefly, indicated cells were grown on confocal dishes (Genetix Biotech Asia Pvt.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence staining and confocal microscopy were performed as described previously ( 12 , 27 , 28 , 63 , 64 ). Briefly, cells were fixed with 4% paraformaldehyde for 20 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanistically, it was found to be a strong mTOR inhibitor by inducing apoptosis via mitochondrial dependent pathway [43]. In addition, Kundu et al, have shown the validation of a new class of quinoline-based topoisomerase 1 (Top1) inhibitor which possesses the highest human Top1 inhibition activity [44]. Topoisomerase I (PDB ID: 1T8I) is complex with the standard pre-bonded top I poison camptothecin as a co-crystal in a planar geometry with the important residues Arg-364, Asp-533 and Thr-718 in active site of 1T8I.…”
Section: Discussionmentioning
confidence: 99%